Combined renal clear cell and papillary carcinoma with neuroendocrine dedifferentiation: a very rare entity - GuL, Tahmina (International Journal of Pathology, 2024)
Background: There are only few documented cases of neuroendocrine differentiation in clear cell renal cell carcinoma .Methods: This is a case report of a combined renal clear cell and papillary carcinoma with neuroendocrine differentiation arising in an 81-year-old male.Results: Immunohistochemistry revealed positivity for PAX8, AMACR and CD10. RCC, synaptophysin, chromogranin, WT-1, CK20, CK7, HMW CK, desmin, CD117 and PAX-2 were all negative. Immunoreactivity for NSE, CD56 and vimentin in the spindle cell component was noted. Ki-67 reactivity was variable.Conclusion: It is suggested that immunohistochemistry for neuroendocrine differentiation should be performed in any high grade component of renal cell carcinoma (RCC) to facilitate their identification